-10+z=6z

Simple and best practice solution for -10+z=6z equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -10+z=6z equation:


Simplifying
-10 + z = 6z

Solving
-10 + z = 6z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-6z' to each side of the equation.
-10 + z + -6z = 6z + -6z

Combine like terms: z + -6z = -5z
-10 + -5z = 6z + -6z

Combine like terms: 6z + -6z = 0
-10 + -5z = 0

Add '10' to each side of the equation.
-10 + 10 + -5z = 0 + 10

Combine like terms: -10 + 10 = 0
0 + -5z = 0 + 10
-5z = 0 + 10

Combine like terms: 0 + 10 = 10
-5z = 10

Divide each side by '-5'.
z = -2

Simplifying
z = -2

See similar equations:

| ((X^(4/3))^5 | | X/1000=0.188 | | 192=16t^2 | | X/100=0.01 | | 2p-7=7p+8 | | 31/-0.41ln | | 5p+12=3p+24 | | 4c-5c-8=4-3c | | 2.1=0.0027066x^2+0.042524x+0.098083 | | -31/0.41ln | | 2/5n=6=10 | | 5x-11=54 | | 6r=8+4r | | -6+10q=9q | | -1+5d=7d+7 | | 13y-6=11y+6 | | 1/2y-9=1/7y | | 4y-5=-9 | | x^2+50x+600=936 | | -3+8v=7v | | -5/13x=-19 | | 6f=9f+9 | | 6f=9+9 | | 8(p+10)=96 | | 2(j+2)=6 | | (10j-7)-(-9+2)= | | 5=9(x-8) | | -10u=9-9u | | (20+x)(30+x)=936 | | 1250n*30=30000 | | w=-4-w | | 15y-2y+y^2+3y= |

Equations solver categories